2007
DOI: 10.1080/10826080601094264
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Effects on the Efficacy of a Program to Prevent Youth Alcohol Use

Abstract: This study examines how neighborhood characteristics affect program efficacy. Data come from a randomized trial of a substance use prevention program called keepin' it REAL, which was administered to a predominantly Mexican American sample of 4,622 middle school students in Phoenix, Arizona, beginning in 1998. Multilevel models and multiple imputation techniques address clustered data and attrition. Among less linguistically acculturated Latinos, living in poorer neighborhoods and those with many single-mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 58 publications
0
10
0
1
Order By: Relevance
“…The evidence proffered by the present research suggests that the SRO aspect of D.A.R.E. will continue to yield successes; reductions in drug and alcohol use and abuse appear to be promising as well (Kulis, Niera, Yabiku, Stromwall, & Marsiglia, 2007;Warren et al, 2006;Yabiku et al, 2007).…”
Section: Discussionmentioning
confidence: 77%
“…The evidence proffered by the present research suggests that the SRO aspect of D.A.R.E. will continue to yield successes; reductions in drug and alcohol use and abuse appear to be promising as well (Kulis, Niera, Yabiku, Stromwall, & Marsiglia, 2007;Warren et al, 2006;Yabiku et al, 2007).…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, although RCTs are the gold standard for assessments, a number of innovations and improvements in the application of this design might be necessary to strengthen evidence for MHPSS. These improvements would be: the use of multilevel statistics to disentangle contextual effects on individual wellbeing, especially for assessment of commonly implemented psychosocial interventions at the base of the intervention pyramid; 84 integration of the study of moderators and mediators in assessment studies to examine how interventions achieve their effects; 52,58 and time series analyses of the psychosocial effect of social interventions. 85 …”
Section: Resultsmentioning
confidence: 99%
“…Neighborhood level social disorganization has consistently been linked to substance use in the prior literature (Chow, 1998;Crum et al, 1996;Ennett et al, 1997;Kadushin et al, 1998;Leventhal & Brooks-Gunn, 2000;Raudenbush & Sampson, 1999). A recent development in this line of inquiry by Yabiku et al (2007) suggested that substance abuse becomes a validated behavior and emerges as a viable option or coping mechanism for hunger, crime, violence, family issues, health issues, and substandard living conditions in socially disorganized neighborhoods where adolescents observe adults misusing drugs and alcohol. Neighborhood disorder also influences substance use by increasing the availability, as well as acceptability of drugs (Jang & Johnson, 2001), and prior research has found neighborhood context to be a key predictor of substance use for ethnic minority adolescents (Gruenewald, Millar, Ponicki, & Brinkley, 2000;Treno, Alaniz, & Gruenewald, 2000).…”
Section: Theoretical Reviewmentioning
confidence: 95%
“…This development has been most notable within three theoretical domains: social bonding theory (Billingham, Wilson, Gross, & William, 1999;Durkin, Wolfe, & Lewis, 2006), social learning theory (Earleywine, 1995;Grube, Chen, Madden, & Moran, 1995;Martino, Collins, Ellickson, Schell, & McCaffrey, 2006;Morrison, Simpson, Gillmore, Wells, & Hoppe, 1996;Smith & Goldman, 1994), and social disorganization theory (Chow, 1998;Crum, Lillie-Blanton, & Anthony, 1996;Ennett, Flewelling, Lindrooth, & Norton, 1997;Jang & Johnson, 2001;Kadushin, Reber, Saxe, & Livert, 1998;Leventhal & Brooks-Gunn, 2000;Raudenbush & Sampson, 1999;Yabiku et al, 2007).…”
mentioning
confidence: 96%